DEVELOPMENT OF TEACHING MATERIALS IN WRITING DESCRIPTIVE TEXTS OF VOCATIONAL SCHOOL STUDENTS - Risnawaty Risnawaty; Yulia Arfanti; Milisi Sembiring; Roswani Siregar; Heni Subagiharti (Universitas Islam Sumatera Utara (UISU), 2021)
The objective of the study is to develop the teaching materials in writing descriptive texts in Grade X students of SMK Binaan UMN Al-Washliyah 3, Medan. The study is conducted by the Development Research method, and the evaluators are the instructors of the Indonesian Subject (specific instructors), and the subjects are Grade X students. Pre-test and post-test are done to find out the effectiveness of the result. The result of the pre-test shows that the average score is 67% with the category of satisfactory; the result of the post-test shows that the average score is 85% with the category of distinction. The process of developing teaching materials includes three aspects of assessment: 1) teaching materials, 2) presentation, and 3) language structure. The validation of material experts includes content with an average score of 4.9% and a percentage of 82.2% with the category of distinction. The feasibility of presenting teaching materials has an average score of 113% with the category of distinction, and the language element has an average score of 11.4% with the category of distinction. The conclusion indicates that the design for developing teaching materials of descriptive texts by using a scientific approach in the subject of Indonesian is very effective.